Sistem Pendukung Keputusan Seleksi Kandidat Tenaga Kesehatan Teladan dengan Menerapkan Metode WASPAS - Hardian Syahputra (Journal of Decision Support System Research, 2024)
The Sei Suka Health Center, Batu Bara Regency, determines health workers by looking at the conditions of the candidates to be selected, whether they are eligible to be appointed as candidates for health workers or not. and must have very good, good, good enough, not good criteria. In addition, the Sei Suka Health Center, Batu Bara Regency, is still selecting candidates for health workers in Batu Bara Regency, which is still done manually, in the sense of recording (Handwriting) data on health workers who will be selected as potential health workers, this is less effective and hinders the work of the Puskesmas. Sei Suka Batu Bara Regency in selecting candidates for health workers manually. Because this SPK provides decision-making information in semi-structured situations. The solution to the problems that are happening, the authors take the Decision Support System (DSS), which is an information system that provides information, a decision-making system in semi-structured situations and unstructured situations where no one knows how to make decisions. There are several methods that can be used in a Decision Support System (DSS), including the WP, WASPAS, MOORA, TOPSIS, ELECTR, PROMETHEE, AHP methods. The results of the study show that the existence of a Decision Support System for Selection of Exemplary Health Worker Candidates Using the WASPAS Method can be carried out quickly, precisely, and objectively. The final result after applying the WASPAS method concluded that alternative A2 in the name of Nurasiah Rais, Am.Keb obtained the highest value, namely 0.3827.